PeaceTech: Digital Transformation to End Wars - Bell, Christine (Springer Nature, 2024)
Why are we willing to believe that technology can bring about war... but not peace? PeaceTech: Digital Transformation to End War is the world's first book dealing with the use of technological innovation to support peace and transition processes. Through an interwoven narrative of personal stories that capture the complexity of real-time peace negotiation, Bell maps the fast-paced developments of PeaceTech, and the ethical and practical challenges involved. Bell locates PeaceTech within the wider digital revolution that is also transforming the conduct of war. She lays bare the 'double disruption' of peace processes, through digital transformation, and through changing conflict patterns that make processes more difficult to mount. Against this backdrop - can digital peacebuilding be a force for good? Or do the risks outweigh the benefits? PeaceTech provides a 12-Step Manifesto laying out the types of practice and commitment needed for successful use of digital tools to support peace processes. This open access book will be invaluable primer for business tech entrepreneurs, peacebuilders, the tech community, and students of international relations, informatics, comparative politics, ethics and law; and indeed for those simply curious about peace process innovation in the contemporary world.